Fertiliser in small doses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Using fertiliser in countries of the South is often fraught with problems. The high cost of these industrial products is often crippling for farmers, who are reluctant to make such an investment, given the uncertain climate...